Fast-Fed Variability: Insights into Drug Delivery, Molecular Manifestations, and Regulatory Aspects - Nagarjun Rangaraj; Sunitha Sampathi; Vijayabhaskarreddy Junnuthula; Praveen Kolimi; Preethi Mandati; Sagar Narala; Dinesh Nyavanandi; Sathish Dyawanapelly (MDPI AG, 2022)
Among various drug administration routes, oral drug delivery is preferred and is considered patient-friendly; hence, most of the marketed drugs are available as conventional tablets or capsules. In such cases, the administration of drugs with or without food has tremendous importance on the bioavailability of the drugs. The presence of food may increase (positive effect) or decrease (negative effect) the bioavailability of the drug. Such a positive or negative effect is undesirable since it makes dosage estimation difficult in several diseases. This may lead to an increased propensity for adverse effects of drugs when a positive food effect is perceived. However, a negative food effect may lead to therapeutic insufficiency for patients suffering from life-threatening disorders. This review emphasizes the causes of food effects, formulation strategies to overcome the fast-fed variability, and the regulatory aspects of drugs with food effects, which may open new avenues for researchers to design products that may help to eliminate fast-fed variability.